Utilização da plataforma arduino para a automatização de um circuito RLC acoplado para coleta de dados - Oliveira, Júlio César Gomes (Universidade Federal de São Carlos, 2022)
The increasing integration of technology in science teaching laboratories, through software and computerization, has motivated teachers and students to develop technical skills involving scientific computing. In this work we present such integration using a simple and low cost experiment. In particular, we present how the data collection procedure in a coupled two-loop RLC resonant circuit can be computerized using the Arduino platform. To obtain the system parameters for the implementation of the experiment, it was necessary to perform simulations of the proposed circuit using the Multisim electronic circuit simulator. After verifying the same behavior of the system reported in the literature, the real circuit was implemented and the data collection was performed manually using an oscilloscope. The results showed that the real circuit exhibits the same phenomenology observed in the simulations. Then, the computerization of the data collection procedure was performed in the experiment using the arduino platform together with the PLX-DAQ software, to generate a graph in real time that describes the behavior of the system. The experimental results obtained manually and by the computerized system showed excellent agreement, showing that the computerization process does not interfere with the behavior of the system. Such process proved to be very advantageous, as it reduced the data collection procedure from two hours to just fifteen minutes. Additionally to the process of integration between experimentation, theory, use of technology and computer simulation, the computerization implemented in the analyzed circuit can help the teacher to considerably reduce the time spent for repetitive activities in an experiment, such as data collection, in such a way that the lesson time can be better used for analysis and discussion of results.
Use of the Arduino platform for the computerization of a coupled RLC circuit for data collection
Keywords: Experimentação; Simulação Computacional; Automatização; Ressonância; Ensino de Física; Experimentation; Computational Simulation; Computerization; Resonance; Physics Teaching; CIENCIAS EXATAS E DA TERRA::FISICA